Comparative typologyand itscontent, subject matter and methods. Principles and methods of comparative typological analysis - Kamalitdinovna, Djabbarova Nozima; Bahramovna, Mamadalieva Zuhra; Normurodovna, Jalalova Feruza; Sherzod kizi, Israilova Dilkhumor (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on the comparative typology of English, Uzbek and Russian and discusses the formation of comparative typology as a science, its methods of analysis and the relations of it with other linguistic subjects. Besides there are discussed certain correlations between the comparative typology and the other branches of general linguistics based onthe method of comparison (comparative method).